THE EFFECT OF GAME CREATION MECHANISMS ON E-LEARNING DURING THE CORONA PANDEMICWITH THE MEDIATING ROLE OF STUDENTS' MENTAL INVOLVEMENT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study was to evaluate the effect of game creation mechanisms on e-learning during the corona epidemic with the mediating role of students' mental involvement and with a practical approach in the Faculty of Management, University of Tehran. The research literature and studies indicate that play-making mechanisms affect e-learning during the corona epidemic through students' mental engagement. A questionnaire consisting of 17 questions with a five-point Likert scale was used to collect data. To evaluate the validity of the questionnaire, four methods of content validity, structural validity, convergent validity and divergent validity have been used. First, the questionnaire was approved from the perspective of experts in terms of content validity. Then the validity of the structure was performed using the external model. The value of AVE of all variables was above 0.5 and convergent validity was confirmed. Cronbach's alpha and composite reliability were calculated for reliability. Cronbach's alpha coefficient of the questionnaire was calculated to be 0.912 and the CR value of all variables was obtained above 0.7. Therefore, the reliability of the questionnaire has been evaluated as desirable. The statistical population of this research includes all students of the Faculty of Management, University of Tehran and the questionnaire was randomly given to 400 students. To test the research hypotheses, the technique of partial least squares and Smart Pls software have been used. Game creation mechanisms (competition and cooperation) are significantly associated with students' mental involvement and with e-learning during the corona epidemic. Students' mental engagement is significantly associated with e-learning during the corona epidemic. Students' mental engagement mediates the mechanisms of game creation (competition and collaboration) and e-learning during the corona epidemic.